1992
DOI: 10.1093/ije/21.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Self and Proxy Reporting of Morbidity Data: A Case Study from Beirut, Lebanon

Abstract: We compared the self-reported illnesses (heart disease, back pain, rheumatoid arthritis, hypertension, and pulmonary disease) and smoking histories of 100 cases and 100 controls matched for age and sex with reports of this information from proxy informants from the same household in two areas in the city of Beirut. In addition, both cases and controls were given physical examinations to evaluate the accuracy of the responses. The level of agreement between the responses of subjects and of their informants vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…39,40 Another limitation is that undiagnosed hypertension and other risk factors were not accounted for, since 6.4% of respondents admitted never having their BP measured. A major drawback to our study is the absence of any clinical measurement for the documentation of hypertension; however, several studies carried out both nationally 41 and internationally [42][43][44][45][46] to assess the validity of self-reported chronic diseases including hypertension revealed a moderate to substantial agreement between questionnaire data and either clinical examinations 42,43 or medical records. [44][45][46] A study carried out in Beirut 41 to assess the agreement between selfreported morbidity and physical examination, revealed that heart disease had the highest agreement followed by hypertension and concluded that the health interview survey was reasonably accurate for data collection of chronic conditions, which are clearly defined for the population.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Another limitation is that undiagnosed hypertension and other risk factors were not accounted for, since 6.4% of respondents admitted never having their BP measured. A major drawback to our study is the absence of any clinical measurement for the documentation of hypertension; however, several studies carried out both nationally 41 and internationally [42][43][44][45][46] to assess the validity of self-reported chronic diseases including hypertension revealed a moderate to substantial agreement between questionnaire data and either clinical examinations 42,43 or medical records. [44][45][46] A study carried out in Beirut 41 to assess the agreement between selfreported morbidity and physical examination, revealed that heart disease had the highest agreement followed by hypertension and concluded that the health interview survey was reasonably accurate for data collection of chronic conditions, which are clearly defined for the population.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados, ao contrário do esperado, podem ter como origem diferenças nas concepções sobre saú-de e doença, ou o significado que tem para os respondentes, na perspectiva qualitativa ou quantitativa, as manifestações biológicas ou emocionais. 12 Fracas concordâncias podem também ser atribuídas a caracterís- 7 quando esses conflitos produzirem distanciamento, é possível haver ainda menor concordância.…”
Section: Discussionunclassified
“…Dentre os fatores que determinariam baixa confiabilidade entre as informações de pais e filhos adolescentes, especialmente quando estes últi-mos trabalham, estaria a independência e o afastamento do convívio dos pais que se acentua nessa etapa da vida. 7 A questão de se investigar se informantes adolescentes respondiam de modo semelhante ao de suas mães surgiu no contexto de um inquérito sobre trabalho e saúde, e a necessidade de garantia da qualidade das informações obtidas com questionários. No presente estudo, estimou-se a confiabilidade e a ocorrência de vieses de informação entre respostas obtidas de adolescentes e suas respectivas mães.…”
Section: Introductionunclassified
“…Check lists of this sort have been widely used in previous population-based studies. Good concordance between checklists and medical records has been shown (Heliovaara et al 1993;Halabi et al 1992;Kriegsman et al 1996). The number of physical health conditions was coded into categories of 0, 1, 2, 3, 4, 5, 6 or more.…”
Section: Physical Health Conditionsmentioning
confidence: 99%